HEURISTIC ALGORITHM FOR MULTI STACK NESTING PROBLEM ON NC ROUTER MACHINE AT PT. DIRGANTARA INDONESIA - Ali, Irfansyah
Nesting is the process of forming a cutting pattern by allocating parts into sheets without overlapping. The nesting process is one of the important step of production processes at PTDI. The nesting process at PTDI is done right before the cutting stage (NC Routing) on the CNC Router. The NC Routing at PTDI still produces a large amount of material waste, which actually can be minimized. By minimizing the waste, huge economic savings can be achieved. This can be achieved with an efficient nesting approach and accordance to the practical conditions encountered. This means that the cutting pattern must be compact, where each part is placed close to each other, well allocated, utilize the space, and also the approach must consider the constraints encountered. The amount of waste generated occurs because the nesting plan is not efficient and not in accordance yet with several practical conditions. Among them are considerations in selecting an efficient sheet and considering the reuse of cutting residues. The CNC Router machine has the capacity to process a maximum of 3 layers material in one batch process, but PTDI has not carried out optimally. Which if PTDI utilize this capacity, PTDI can minimize processing costs at the NC Routing. PTDI uses many parts, in a large data set, in its production processes. It is known that the exact approach is not efficient in finding solutions to nesting problems with large data sets. Therefore, a heuristic approach with consideration of practical conditions is needed to obtain an effective and efficient practical solution. This study uses the models and algorithms in the literature Liu et al. (2011), Andrade et al. (2014), Chen et al. (2019), Sumetthapiwat et al. (2020), and Aribowo et al. (2021) as a reference in the development of the best-fit heuristic algorithm with practical considerations of variable-bin size, usable leftover, and stacked sheets. The algorithm is used in finding solutions to nesting problems for the NC Routing at PTDI. Compared with the solution generated by the optimal model Aribowo et al. (2021), the proposed algorithm can produce a solution close to optimal with a difference of 6.99-10.59%. And based on trials using PTDI production data, the proposed algorithm can provide an efficiency of 45%.